2020
DOI: 10.1088/1361-6668/aba354
|View full text |Cite
|
Sign up to set email alerts
|

Mixed state properties analysis in AC magnetic field of strong pinning Fe(Se,Te) single crystal

Abstract: The fundamental harmonic of the AC magnetic susceptibility of a Fe(Se,Te) single crystal iron based superconductor has been studied at different AC field amplitudes and frequencies with and without a superimposed DC magnetic field with the aim of analyzing its superconducting properties that can be also suitable for power applications such as the critical current density and the pinning energy in AC regime. From the analysis of the fundamental Cole-Cole plots a finite influence of flux creep phenomena has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…5(b), J c at 1 T in bulk FTS is very close to that in our thin-film devices with d 100 nm. Therefore, we analyze J c (T ) using the weak collective pinning theory, as discussed for bulk FTS in previous works [4][5][6][7][8]. In the theoretical approach proposed by Griessen et al [22], J c (T ) in the moderately low field region, where the strong pinning can be ignored and the motion of single vortex is essential, is given as…”
Section: B Weak Collective Pinningmentioning
confidence: 99%
See 3 more Smart Citations
“…5(b), J c at 1 T in bulk FTS is very close to that in our thin-film devices with d 100 nm. Therefore, we analyze J c (T ) using the weak collective pinning theory, as discussed for bulk FTS in previous works [4][5][6][7][8]. In the theoretical approach proposed by Griessen et al [22], J c (T ) in the moderately low field region, where the strong pinning can be ignored and the motion of single vortex is essential, is given as…”
Section: B Weak Collective Pinningmentioning
confidence: 99%
“…Among all kinds of IBSs, the iron-based chalcogenide FeTe 1−x Se x with x = 0.4 ∼ 0.5 (FTS) has the simplest crystal structure with only FeCh (Ch = Se or Te) layers. There have been many reports on bulk [3][4][5][6][7][8][9][10][11][12] and thinfilm [13][14][15][16] FTS single crystals, which enable a detailed discussion of the pinning mechanism. Although the critical temperature T c is not so high, the upper critical field is comparable to other IBSs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that a further analysis of the complex AC susceptibility data allows one to obtain the London penetration depth and therefore the superfluid density, thus enabling the validation of theories and models concerning the mechanisms of superconductivity in the IBS. For this goal, the high frequency of this technique offers an advantage with respect to conventional AC susceptometry, for which the determination of is challenging [ 16 ] because of the long wavelength and the geometry associated with those experiments [ 17 ], which is more suitable for the study of vortex physics and pinning [ 18 , 19 , 20 ] and of nonlinearity [ 21 , 22 ]. In Section 3 of this paper, we present and discuss the characterization of several IBS systems, belonging to different IBS families.…”
Section: Introductionmentioning
confidence: 99%